Green ink an introduction to environmental journalism - Frome, Michael (Univ. of Utah Press, 1998)
"Equal parts anecdote, advice, personal testimony, and nuts and bolts instruction, Green Ink will inspire all who care about the environment. Having encountered censorship and dismissal for his unstinting defense of the environment, Michael Frome writes with passion and conviction about advocacy journalism. He reports candidly on the rewards and challenges to be expected in its pursuit, noting the important contributions of such varied voices as Rachel Carson and Bernard DeVoto, John Muir and Edward Abbey, William Cullen Bryant and Walt Whitman, Studs Terkel and Aldo Leopold, as well as many contemporary investigative environmental writers. Green Ink serves as a valuable primer for those who aspire to write about the environmental issues and crises facing us today."--BOOK JACKET.